#radonc: Growth of the global radiation oncology Twitter network. (November 2021) - Prabhu, Arpan V.; Beriwal, Sushil; Ahmed, Wasim; Ayyaswami, Varun; Simcock, Richard; Katz, Matthew S.
Highlights: Global #radonc community grew from 23 countries in 2014 to 116 in 2019. Focused discussion related to #radonc outpaced growth of general twitter use. #radonc has grown into a self-sustaining community. Abstract: Introduction: Social media connects people globally and may enhance access to radiation oncology information. We characterized the global growth of the radiation oncology Twitter community using the hashtag #radonc. Materials and Methods: We analyzed all public tweets bearing the hashtag #radonc from 2014 to 2019 using Symplur Signals. We collected data on #radonc activity and growth, stakeholder distribution, user geolocation, and languages. We obtained global Twitter user data and calculated average annual growth rates for users and tweets. We analyzed growth rates by stakeholder. We conducted thematic analysis on a sample of tweets in each three-year period using frequently occurring two-word combinations. Results: We identified 193, 115 tweets including #radonc composed by 16, 645 Twitter users. Globally, users wrote in 35 languages and came from 122 countries, with the known highest users from the United States, United Kingdom, and Spain. Use of #radonc expanded from 23 countries in 2014 to 116 in 2019. The average annual growth rate in #radonc users and tweets was 70.5% and 69.2%, respectively. The annual growth rate of #radonc users was significantly higher than for all Twitter users ( p  = 0.004). While doctors were the source of 46.9% of all tweets, research and government organizations had annual increases in tweet volume of 84.6% and 211.4%, respectively. From 2014 to 2016, promotion of the radiation oncology community was the most active theme, though this dropped to 7th in 2017–2019 as discussion increased regarding aspects of radiation and treated disease sites. Conclusion: Use of #radonc has grown rapidly into a global community. Focused discussion related to radiation oncology has outpaced the growth of general Twitter use, both among physicians and non-physicians. #radonc has grown into a self-sustaining community. Further research is necessary to define the risks and benefits of social media in medicine and to determine whether it adds value to oncology practice.